Predictive performance of interferon-gamma release assays and the tuberculin skin test for incident tuberculosis: an individual participant data meta-analysisResearch in context - Yohhei Hamada; Rishi K. Gupta; Matteo Quartagno; Abbie Izzard; Carlos Acuna-Villaorduna; Neus Altet; Roland Diel; Jose Dominguez; Sian Floyd; Amita Gupta; Helena Huerga; Edward C. Jones-López; et al. (EClinicalMedicine, 2023)
Summary: Background: Evidence on the comparative performance of purified protein derivative tuberculin skin tests (TST) and interferon-gamma release assays (IGRA) for predicting incident active tuberculosis (TB) remains conflicting. We conducted an individual participant data meta-analysis to directly compare the predictive performance for incident TB disease between TST and IGRA to inform policy. Methods: We searched Medline and Embase from 1 January 2002 to 4 September 2020, and studies that were included in previous systematic reviews. We included prospective longitudinal studies in which participants received both TST and IGRA and estimated performance as hazard ratios (HR) for the development of all diagnoses of TB in participants with dichotomised positive test results compared to negative results, using different thresholds of positivity for TST. Secondary analyses included an evaluation of the impact of background TB incidence. We also estimated the sensitivity and specificity for predicting TB. We explored heterogeneity through pre-defined sub-group analyses (e.g. country-level TB incidence). Publication bias was assessed using funnel plots and Egger's test. This review is registered with PROSPERO, CRD42020205667. Findings: We obtained data from 13 studies out of 40 that were considered eligible (N = 32,034 participants: 36% from countries with TB incidence rate ≥100 per 100,000 population). All reported data on TST and QuantiFERON Gold in-Tube (QFT-GIT). The point estimate for the TST was highest with higher cut-offs for positivity and particularly when stratified by bacillus Calmette–Guérin vaccine (BCG) status (15 mm if BCG vaccinated and 5 mm if not [TST5/15 mm]) at 2.88 (95% CI 1.69–4.90). The pooled HR for QFT-GIT was higher than for TST at 4.15 (95% CI 1.97–8.75). The difference was large in countries with TB incidence rate <100 per 100,000 population (HR 10.38, 95% CI 4.17–25.87 for QFT-GIT VS. HR 5.36, 95% CI 3.82–7.51 for TST5/15 mm) but much of this difference was driven by a single study (HR 5.13, 95% CI 3.58–7.35 for TST5/15 mm VS. 7.18, 95% CI 4.48–11.51 for QFT-GIT, when excluding the study, in which all 19 TB cases had positive QFT-GIT results). The comparative performance was similar in the higher burden countries (HR 1.61, 95% CI 1.23–2.10 for QFT-GIT VS. HR 1.72, 95% CI 0.98–3.01 for TST5/15 mm). The predictive performance of both tests was higher in countries with TB incidence rate <100 per 100,000 population. In the lower TB incidence countries, the specificity of TST (76% for TST5/15 mm) and QFT-GIT (74%) for predicting active TB approached the minimum World Health Organization target (≥75%), but the sensitivity was below the target of ≥75% (63% for TST5/15 mm and 65% for QFT-GIT). The absolute differences in positive and negative predictive values between TST15 mm and QFT-GIT were small (positive predictive values 2.74% VS. 2.46%; negative predictive values 99.42% VS. 99.52% in low-incidence countries). Egger's test did not show evidence of publication bias (0.74 for TST15 mm and p = 0.68 for QFT-GIT). Interpretation: IGRA appears to have higher predictive performance than the TST in low TB incidence countries, but the difference was driven by a single study. Any advantage in clinical performance may be small, given the numerically similar positive and negative predictive values. Both IGRA and TST had lower performance in countries with high TB incidence. Test choice should be contextual and made considering operational and likely clinical impact of test results. Funding: YH, IA, and MXR were supported by the National Institute for Health and Care Research (NIHR), United Kingdom (RP-PG-0217-20009). MQ was supported by the Medical Research Council [MC_UU_00004/07].